1990
DOI: 10.3109/02713689008999606
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic assessment of an ophthalmic gelling vehicle in man and rabbit

Abstract: Studies of the rate of clearance of a gellan gum formulation (Gelrite) radiolabelled by the inclusion of technetium-99m labelled diethylenetriaminepentaacetic acid were carried out in volunteer subjects and in rabbits. Disposition was followed by gamma scintigraphy and compared with 0.5% w/v hydroxyethylcellulose (HEC) solution and isotonic saline administered to the same subjects. Clearance of all solutions was found to follow bi-exponential kinetics with differences in clearance rates between the two species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…However, in another study, we examined contrast sensitivity function after instillation of timolol gel-forming solution, which is the same drug used in this study, and found that the gel-forming solution significantly decreased contrast sensitivity for at least 5 min following instillation, whereas standard timolol solution (without gels) did not reduce contrast sensitivity. 34 On the basis of this finding, it seems quite probable that eye ointment decreases contrast sensitivity during 6 h after application because HOAs and FI at 6 h after administration of eye ointment were still higher than those at 5 min after the gel-forming solution in the present study. The verification of such a long visual deterioration requires further studies.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, in another study, we examined contrast sensitivity function after instillation of timolol gel-forming solution, which is the same drug used in this study, and found that the gel-forming solution significantly decreased contrast sensitivity for at least 5 min following instillation, whereas standard timolol solution (without gels) did not reduce contrast sensitivity. 34 On the basis of this finding, it seems quite probable that eye ointment decreases contrast sensitivity during 6 h after application because HOAs and FI at 6 h after administration of eye ointment were still higher than those at 5 min after the gel-forming solution in the present study. The verification of such a long visual deterioration requires further studies.…”
Section: Discussionsupporting
confidence: 46%
“…33 It is considered that such dynamics of gels on ocular surface induces transient changes in ocular HOAs. 24,34 On the other hand, as eye ointment is not fragmented by blinks as gels, it is slowly cleared from the interpalpebral space through the lacrimal drainage system or by moving onto the lid skin. 1 Furthermore, its high viscosity retards these clearances.…”
Section: Discussionmentioning
confidence: 99%
“…Gellan gum is an anionic heteropolysaccharide that gives a colorless and transparent solution and forms a gel when it comes in contact with monovalent and divalent cations present in tears [5,13]. In this study, TMGS showed significant changes at 24 hr after the first instillation.…”
mentioning
confidence: 55%
“…Studies on the medical and pharmaceutical applications of gellan gum have also been reported. For example, it has been used as a scaffold material for the application of tissue engineering 232,233 , as a vehicle for ophthalmic drugs 234,235 , and in eye drops 236 .…”
Section: Gellan Gummentioning
confidence: 99%